Association between socioeconomic indicators and pulse wave velocity (PWV) measurements in population studies: a systematic review and meta-analysis - Photiou, Galatia; Kouis, Panayiotis; Papasavva, Zoi; Panagiotakos, Demosthenes B.; Middleton, Nicos; Panayiotou, Andrie G. (My University, 2025)
Arterial stiffness, which is estimated by pulse wave velocity (PWV), has been associated with cardiovascular morbidity and mortality; however, there is sparse literature on socioeconomic (SES) indicators and PWV.
Keywords: Arterial stiffness; Education; Income; Pulse wave velocity; socioeconomic status; Socioeconomic indicators